Properties of Carbon Xerogels Supported Cobalt‐Based Catalysts and Their Performance in CO Hydrogenation Reaction. Issue 37 (1st October 2019) - Han, Yaoyao; Jin, Yan; Hong, Jingping; Jin, Shiwei; Zhang, Yuhua; Li, Jinlin
Abstract: Carbon xerogels (C−X), which synthesized by a convenient method with moderate porous texture and high surface area, was used as potential support for cobalt‐based catalysts, and the catalytic performance was studied by CO hydrogenation. The use of activated carbon (AC) and carbon nanotubes (CNTs) as supports was also investigated for comparison. The catalysts were prepared by incipient wetness impregnation method, and adjustment of cobalt dispersion on Co/C−X was achieved by variation of the decomposition approaches of cobalt nitrate. Characterization and CO hydrogenation results showed that C−X is a good candidate as catalyst support, it could homogeneously disperse both big cobalt particles and small ones. And the supported Co/C−X catalysts had either higher catalytic activity or better reaction stability, in comparison with CNTs and AC supported counterparts. Glow discharge plasma assisted decomposition of cobalt nitrate led to the formation of much smaller cobalt particles, and due to the inert properties of carbon materials, the Co/C−X‐P catalyst showed both higher cobalt dispersion and cobalt reducibility than the calcined counterpart, and thus presented a much higher CO hydrogenation activity with good reaction stability as well. Abstract : Carbon xerogels is a good candidate as catalyst support, it could homogeneously disperse both big cobalt particles and small ones. Glow discharge plasma assisted decomposition of cobalt nitrate resulted in the formation of much smaller cobalt particles. Combination of plasma treatment and inert properties of carbon xerogels led to both higher cobalt dispersion and cobalt reducibility in corresponding catalyst, and thus presented a much higher CO hydrogenation activity with good reaction stability as well.